Proposal for a Humanization Model based on Personal Competencies: HUMAS Model (European Journal of Health Research, 2019)
Although today the concept of humanization is very present in the care environment, there is no clear definition of what can be understood by humanizing care. The aim of collaborating in the realization of a term that has a clear multifactorial composition, the creation of a model to explain the skills and attitudes that must be developed by a healthcare professional to incorporate Humanization in the exercise of his profession. In the proposed model, humanization is defined as a set of personal competences that allow the development of professional activity, within the health field, ensuring dignity and respect for the human being. It is therefore an activity focused on the improvement of health care, both physical, mental and emotional, aimed at patients and relatives, as well as the healthcare professionals themselves. The theoretical model proposed HUMAS focuses on psychological processes, on the personal skills that train health professionals to offer the patient quality care. Thus, the professional, with all the resources available in the social and health system and in the patient’s environment, it also requires the acquisition and development of personal skills, including optimism, sociability, emotional understanding, self-efficacy and involvement, understood as essential to contribute to positive professional performance, based on humanization, such as the HUMAS model.